The Ability of Riboflavin-Overproducing Lactiplantibacillus plantarum Strains to Survive Under Gastrointestinal Conditions - Hernández-Alcántara, Annel M.; Pardo, Sandra; Mohedano, Mari Luz; Vignolo, Graciela M.; de Moreno de LeBlanc, Alejandra; LeBlanc, Jean Guy; Aznar, Rosa; López, Paloma (Frontiers in Microbiology, 2020)
Riboflavin, vitamin B2, is essential for humans and has to be obtained from the diet. Some lactic acid bacteria (LAB) produce this vitamin, and they can be used for in-situ fortification of foods. This could be an alternative to supplementation with chemically synthesized vitamin, to palliate riboflavin deficiencies in specific groups of people. Moreover, if the producing LAB could survive in the gastrointestinal stress (GIT) they could be added as probiotics in this environment. In the present study we tested two riboflavin-overproducing Lactiplantibacillus plantarum strains (M5MA1-B2 and M9MG6-B2), spontaneous mutants of LAB isolated from chicha, a traditional Andean beverage. These two LAB, and also their isogenic strains M5MA1-B2[pRCR12] and M9MG6-B2[pRCR12], expressing the mCherry protein from the pRCR12 plasmid, were evaluated in vitro under simulated GIT conditions. Among other, specifically developed protein fluorescence assays were used. The four LAB showed similar levels of adhesion (>6.0%) to Caco-2 cells, higher than that of the probiotic Lacticaseibacillus rhamnosus GG strain (4.51%). Thus, LAB biofilm formation was assessed in the labelled cells by intracellular mCherry fluorescence and in the unlabelled parental strains by crystal violet staining. Both methods detected the formation of consistent biofilms by the L. plantarum strains. The quantification of mCherry fluorescence was also used to analyze LAB auto-aggregation properties. High levels of auto-aggregation were detected for both M5MA1-B2[pRCR12] and M9MG6-B2[pRCR12]. Survival of LAB included in a commercial cereal-based food matrix (Incaparina) under GIT conditions was also evaluated. The four LAB were resistant in vitro to the stomach and intestinal stresses, and proliferated in this environment, indicating a protective and nutritional effect of the Incaparina on the bacteria. Also, M9MG6-B2 survival in the presence or absence of Incaparina was evaluated in vivo in a BALB/c mouse model. The administration of the M9MG6-B2 strain alone or together with Incaparina had no adverse effect on the health, growth and/or well-being of the rodents. In addition, an increment in the villus length/crypt depth ratio was observed. The overall results obtained indicate that the LAB studied have probiotic characteristics of interest for the development of functional foods.